Isolation of strach degrading microorganism from local hot spring - Afnil Danial, Ahmad Meri (2008)
This study was performed to isolate starch-degrading microorganism from hot spring which located in Sungai Klah, Perak The objective of this study was to isolate a microorganism that can degrade starch from local hot spring. This research begin with the sample collection from local hot spring and screened for the amylase producer by observing the halo zone appeared around the colonies after pouring with iodine. After that, the microorganism was characterized by using four staining methods which were simple staining, Gram staining, spore staining, and acid-fast staining. In conclusion, the microorganism that had been isolated was rod shaped, Gram positive, spore former, and non acid-fast cells. It can be concluded that microorganism was Bacillus type.